2005
DOI: 10.1626/pps.8.86
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seed Rhizome Size on Growth and Yield of Turmeric (Curcuma longa L.)

Abstract: Turmeric {Curcuma longa L ) plant species produces different sizes of daughter rhizomes (R) and mother rhizomes (MR), which are the only propagules (seed) for its cultivation. Here, we evaluated the effects of seed rhizome size on growth and yield of turmeric. Daughter rhizomes of 5-50 g (R-5 g~R-50 g) and mother rhizomes of 48-52 g (MR) were tested. The heavier the R up to 40 g, die better the plant growth, and die plants from die R-30 g, R-40 g, R-50 g and MR grew similarly well. The seed rhizomes with a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
32
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 7 publications
10
32
0
1
Order By: Relevance
“…Similarly, Sarker et al (2001) reported that longer photosynthesis was the key factor of higher rice-yield. Higher shoot biomass resulted in a higher yield, which was in agreement with the results of previous studies (Ishimine et al, 2003;Hossain et al, 2005a). Dark-red soil 141 ± 6bc 18.7 ± 2.6cd 2.5 ± 0.5b 230 41.2 ± 4.7b 39 ± 6d…”
Section: Methodssupporting
confidence: 92%
“…Similarly, Sarker et al (2001) reported that longer photosynthesis was the key factor of higher rice-yield. Higher shoot biomass resulted in a higher yield, which was in agreement with the results of previous studies (Ishimine et al, 2003;Hossain et al, 2005a). Dark-red soil 141 ± 6bc 18.7 ± 2.6cd 2.5 ± 0.5b 230 41.2 ± 4.7b 39 ± 6d…”
Section: Methodssupporting
confidence: 92%
“…One turmeric plant requires approximately 0.15 m 2 in field condition for better growth and higher yield (Hossain et al, 2005b), therefore the fertilizers were applied considering this area (0.15 m 2 ), not pot size (0.05 m 2 ). We previously reported that chemical fertilizers of 4 g (N = 1 g, P = 1 g, K = 2 g) per pot in dark-red soil without any compost resulted in poor vegetative growth and low yield of turmeric, and the leaves seemed to be light green (Hossain et al, 2005a). Therefore, the fertilizers at the increased rate have been applied to evaluate their effects on turmeric.…”
Section: 【Short Report】mentioning
confidence: 99%
“…curcumin (Rakhunde et al, 1998) and is considered as an important factor in sensory and consumer acceptance of products (Wang et al, 2009). Besides being a spice crop, it has worldwide demand in cosmetic as well as in medicinal industry (Hossain et al, 2005). Its role as an antimalarial (Nandakumar et al, 2006), anti-inflammatory and antitumor (Gupta et al, 2012) has been well appreciated worldwide and it has also been known to modulate lipid metabolism, which has been implicated in obesity (Alappat & Awad, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…So it is obvious that the selection of right size planting material (length, weight and number of growing buds per seed) is an important factor for turmeric cultivation. Although the standard size of turmeric rhizome for planting is 20-30 g as per the scientific package of practices yet many researchers reported that planting larger turmeric seed rhizomes resulted in higher yield compared to smaller seed rhizomes (Randhawa & Mishra, 1974;Borget, 1993;Hossain et al, 2005). Further, Awasthy & Jessykutty (2017) also reported that a turmeric rhizome bit of approximate weight i.e.…”
Section: Introductionmentioning
confidence: 99%